2022
DOI: 10.1093/jxb/erac077
|View full text |Cite
|
Sign up to set email alerts
|

Advances in field-based high-throughput photosynthetic phenotyping

Abstract: Gas exchange techniques revolutionized plant research and advanced understanding, including associated fluxes and efficiencies, of photosynthesis, photorespiration, and respiration of plants from cellular to ecosystem scales. These techniques remain the gold standard for inferring photosynthetic rates and underlying physiology/biochemistry, although their utility for high-throughput phenotyping (HTP) of photosynthesis is limited both by the number of gas exchange systems available and the number of personnel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 140 publications
0
20
0
1
Order By: Relevance
“…It has been previously shown that more natural variation is seen between genotypes during non-steady-state conditions than steady-state conditions, suggesting that our previous understanding of natural variation for photosynthetic traits may be underestimated (Acevedo-Siaca et al, 2020;McAusland et al, 2020;Cowling et al, 2022). It remains difficult to measure dynamic properties at a high throughput required for field screening, for example by using gas exchange, solar-induced fluorescence, or spectral reflectance; however, this is an active research area (reviewed in Murchie et al, 2018;Fu et al, 2022). Recent advances in very high-throughput laboratory-based methodologies, for example using chlorophyll fluorescence (Ferguson et al, 2020;McAusland et al, 2020), have shown promise if these can be scaled to the field.…”
Section: Dynamic Properties Of Photosynthesis: Induction and Relaxati...mentioning
confidence: 99%
“…It has been previously shown that more natural variation is seen between genotypes during non-steady-state conditions than steady-state conditions, suggesting that our previous understanding of natural variation for photosynthetic traits may be underestimated (Acevedo-Siaca et al, 2020;McAusland et al, 2020;Cowling et al, 2022). It remains difficult to measure dynamic properties at a high throughput required for field screening, for example by using gas exchange, solar-induced fluorescence, or spectral reflectance; however, this is an active research area (reviewed in Murchie et al, 2018;Fu et al, 2022). Recent advances in very high-throughput laboratory-based methodologies, for example using chlorophyll fluorescence (Ferguson et al, 2020;McAusland et al, 2020), have shown promise if these can be scaled to the field.…”
Section: Dynamic Properties Of Photosynthesis: Induction and Relaxati...mentioning
confidence: 99%
“…It has been previously shown that more natural variation is seen between genotypes during non-steady-state conditions than steady-state conditions, suggesting that our previous understanding of natural variation for photosynthetic traits may be underestimated ( Acevedo-Siaca et al , 2020 ; McAusland et al , 2020 ; Cowling et al ., 2022 ). It remains difficult to measure dynamic properties at a high throughput required for field screening, for example by using gas exchange, solar-induced fluorescence, or spectral reflectance; however, this is an active research area (reviewed in Murchie et al , 2018 ; Fu et al , 2022 ). Recent advances in very high-throughput laboratory-based methodologies, for example using chlorophyll fluorescence ( Ferguson et al , 2020 ; McAusland et al , 2020 ), have shown promise if these can be scaled to the field.…”
Section: Individual Source Strength Componentsmentioning
confidence: 99%
“…Machine learning methods have been widely used in the regression and classification issues and have been proven to be fast, accurate, and good at generalization. WA (Bruce et al, 2002), partial least square regression (PLSR) (Fu et al, 2022), and least absolute shrinkage and selection operator (LASSO) (Yang and Bao, 2017) are usually used in HSI studies to reduce the high-dimension hyperspectral data to a few important components that are sensitive to the target parameters.…”
Section: Introductionmentioning
confidence: 99%